Wave effects in double-plane lensing - Ramesh, Rahul; Meena, Ashish Kumar; Bagla, Jasjeet Singh (Journal of astrophysics and astronomy, 2022)
We discuss the wave optical effects in gravitational lens systems with two-point mass lenses in two different planes. We identify and vary parameters (i.e., lens masses, related distances and alignments) related to the lens system to investigate their effects on the amplification factor. We find that due to many parameters, it is not possible to make generalized statements regarding the amplification factor. The best approach for two-plane and multi-plane lensing is to study various possible lens systems case by case to explore the possibilities in the parameter space instead of hoping to generalize the results of a few test cases. We present a preliminary analysis of the parameter space for a two-lens system here.